2009
DOI: 10.1007/s00134-009-1416-5
|View full text |Cite
|
Sign up to set email alerts
|

Patient–ventilator asynchrony during non-invasive ventilation for acute respiratory failure: a multicenter study

Abstract: Patient-ventilator asynchrony is common in patients receiving NIV for acute respiratory failure. Our results suggest that leaks play a major role in generating patient-ventilator asynchrony and discomfort, and point the way to further research to determine if ventilator functions designed to cope with leaks can reduce asynchrony in the clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
246
6
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 282 publications
(268 citation statements)
references
References 29 publications
13
246
6
3
Order By: Relevance
“…Second, as the presence of a nasogastric tube can potentially worsen leaks, this could theoretically have adversely influenced patient-ventilator synchrony during PS. However, in our patients, leak volume during PS (2.9 ± 3 l/min) was lower than previously reported values for PS-NIV [6,9], despite the presence of NAVA nasogastric tubes. Third, since during PS-NIV settings were defined by the clinicians according to their usual procedures, the optimization of expiratory trigger, PSlevel and pressurization ramp can be questioned.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…Second, as the presence of a nasogastric tube can potentially worsen leaks, this could theoretically have adversely influenced patient-ventilator synchrony during PS. However, in our patients, leak volume during PS (2.9 ± 3 l/min) was lower than previously reported values for PS-NIV [6,9], despite the presence of NAVA nasogastric tubes. Third, since during PS-NIV settings were defined by the clinicians according to their usual procedures, the optimization of expiratory trigger, PSlevel and pressurization ramp can be questioned.…”
Section: Discussioncontrasting
confidence: 82%
“…This could potentially have increased the beneficial effect of NAVA on patientventilator synchrony as compared to PS-NIV. However, as shown in a previous study, NIV modes do not succeed in reducing the total number of patient-ventilator asynchronies [6]. Second, as the presence of a nasogastric tube can potentially worsen leaks, this could theoretically have adversely influenced patient-ventilator synchrony during PS.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Raising cycling in our study reduced asynchrony to zero and significantly reduced PEEPi. 20,21 This is consistent with previously published data that showed reduced wasted efforts with conventional set cycling (25% peak flow) 22,23 compared with a higher incidence of non-supported inspiratory effort with short expiration time and …”
Section: Discussionsupporting
confidence: 91%
“…Other studies have also suggested that major asynchrony, including IE, is associated with prolonged mechanical ventilation, unsuccessful weaning, sleep fragmentation, and discomfort [2,12,[18][19][20]. Finally, during noninvasive mechanical ventilation IE are related to nocturnal desaturation and reduced REM sleep [6,21].…”
mentioning
confidence: 99%